Clinical efficacy of autogenous vertebrae-filled peek cage in anterior cervical discectomy and fusion with instrumentation / Xusheng Li ... [et.al]. - Xusheng, Li; Shuid, Ahmad Nazrun; Mohd Miswan, Mohd Fairudz; Xuehua, Zhan; Wenqi, Yuan; Haifeng, Yuan (Universiti Teknologi MARA, Sarawak, 2023)
This study aimed to investigate the clinical efficacy of the autologous vertebral-filled polyetheretherketone (PEEK) cage in anterior cervical discectomy and fusion with instrumentation (ACDFI). The clinical data of 368 patients who received ACDFI from September 2012 to September 2017 were retrospectively analyzed. Based on the material that filled PEEK cage during the surgery, the patients were divided into two groups, the autologous vertebrate group (n =185) and the autologous iliac group (n = 183). The operative time, operative blood loss, postoperative complications in the two groups were recorded and analyzed. The bone graft fusion and postoperative functional outcomes, including scores of modified Japanese Orthopedic Association score (mJOA), Neck Disability Index (NDI), and Visual Analog Scale (VAS) were compared.